Kemitraan Program Penelitian dalam Pengelolaan Sumberdaya Arkeologi di Wilayah Papua - Mahmud, M. Irfan (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Cooperation with other institution as for Balai Arkeologi Jayapura can be solve with strategic program. This cooperation among other things archaeological research and archaeological resource. This cooperation based on needed-each other principle.